The Relationship Between Hypertension and the Occurrence of Aneurysms in AV Shunts in CKD Stage V Patients at RSU Kertha Usadha Singaraja - Eka Dharma Putra, I Putu (International Journal of Advanced Multidisciplinary, 2025)
Chronic Kidney Disease (CKD) stage V patients rely on hemodialysis using arteriovenous (AV) shunts for treatment. However, aneurysms frequently occur as complications, threatening the efficacy of therapy. Hypertension, a prevalent condition in CKD patients, increases the risk of aneurysm formation through sustained high pressure on blood vessel walls. This study investigates the relationship between hypertension and aneurysm occurrence in AV shunts among CKD stage V patients. Method : This cross-sectional observational study was conducted at RSU Kertha Usadha Singaraja, involving 40 CKD stage V patients undergoing hemodialysis. Data collection included medical record reviews, blood pressure measurements, and physical examination for aneurysm detection. The association between hypertension and aneurysm incidence was analyzed using the Chi-square test. Result : Among the 40 participants, 27.5% had aneurysms, with a significant association between uncontrolled hypertension and aneurysm occurrence (p = 0.013). Patients with uncontrolled blood pressure were more likely to develop aneurysms (45%) compared to those with controlled blood pressure (10%). The findings underline the importance of blood pressure management in mitigating aneurysm risk. Conclussion : Uncontrolled hypertension significantly contributes to aneurysm formation in AV shunts among CKD stage V patients. Effective blood pressure management is essential to reduce vascular complications, ensuring better outcomes and sustainability of hemodialysis therapy.